Decision Support for Optimal Repositioning of Containers in a Feeder System - Danijela Tuljak-Suban; Elen Twrdy (Promet (Zagreb), 2008)
The transport of empty containers represents a seriousproblem in the fast growing sphere of maritime container transport.The most widespread type of container transport organizationin maritime transport is the hub and spoke mode, whichenables the transport of a great number of containers via largevessels between hub ports, from where feeder ships transport tosmaller ports that thus gravitate to the central hub port. The articlecontains a detailed analysis of the northern Adriatic portsand the feeder connections with the hub ports of the Mediterranean.A two-level VRPPD (Vehicle Routing Problem withPickup and Delivery) problem is modelled on a graph, wherethe transport of full containers is privileged over the transport ofempty containers. This enables the simulation of the feeder systemin the n01them Adriatic, meaning that it shows the ship'soperator the movement programme with minimal transportcosts for the superfluous empty containers in the complex of theregular transports of full containers in the feeder system.